Monolithic honeycomb ceramic catalyst for hydrogen production by partial oxidation reforming of propane as well as preparation method and application of monolithic honeycomb ceramic catalyst
By coating a catalyst slurry onto a silicon carbide honeycomb ceramic support to prepare an integral honeycomb ceramic catalyst, the problems of complex catalyst processes and low efficiency in existing technologies are solved, and a highly efficient propane partial oxidation reforming reaction is achieved, improving catalytic activity and hydrogen yield.
Patent Information
- Application Number
- CN202511166964.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-20
- Publication Date
- 2025-12-30
- Estimated Expiration
- 2045-08-20
AI Technical Summary
In the existing technology, propane partial oxidation reforming catalysts have problems such as long process chain, poor batch consistency, low utilization of precious metals, low heat/mass transfer efficiency, large pressure drop, easy pulverization of catalysts and insufficient utilization of active sites, making it difficult to operate efficiently in SOFC thermal integrated environment.
A monolithic honeycomb ceramic catalyst was prepared by coating a catalyst slurry onto the pore walls of a silicon carbide honeycomb ceramic support under negative pressure. The slurry contained a noble metal precursor, a composite support, and a binder. The catalyst slurry contained platinum, palladium, nano-cerium oxide, and γ-alumina. The catalyst with a high specific surface area was formed by drying and calcining.
It improves the uniformity of active material distribution in the catalyst, enhances catalytic activity and hydrogen yield, reduces pressure drop, improves catalyst stability and precious metal utilization, and increases propane conversion and output power density.
Smart Images

Figure CN121222453A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of solid oxide fuel cell technology, in particular to a monolithic honeycomb ceramic catalyst for hydrogen production by propane partial oxidation reforming, a preparation method and application thereof. BACKGROUND
[0002] Solid oxide fuel cell (SOFC) has broad prospects in the fields of distributed power generation, transportation and portable power supply, and its anode usually needs high-purity hydrogen or hydrogen-rich syngas as fuel with low risk of carbon deposition. Propane is considered as an ideal carbon-hydrogen raw material for on-site hydrogen production of SOFC due to its high energy density, easy liquefied storage and transportation and other advantages. However, propane partial oxidation reforming (POR) is a complex reaction system involving multiple steps of strong exothermic / absorptive coupling such as C-H bond breaking, C-C bond breaking, oxygen activation and water-gas shift, and can only achieve acceptable conversion rate and hydrogen yield under the conditions of 600-800℃ and 0.1-1.0MPa.
[0003] Currently, the POR catalysts generally used in industry and laboratories still use powder or millimeter-sized granular active components as carriers, and the preparation process usually includes multiple processes such as active metal precursor impregnation-drying-calcination-reduction-tabletting / granulation-screening, which has long process chain, poor batch consistency, and needs additional addition of binder and pore-forming agent, resulting in low utilization rate of noble metal and high cost.
[0004] More importantly, in the SOFC heat integration environment, the traditional granular bed has the following inherent defects: the millimeter-sized particles form tortuous channels, and the pressure drop can reach 20-50kPa when the gas linear velocity is high, which not only increases the air blowing power consumption, but also leads to uneven fuel supply on the anode side of SOFC, reducing the stack efficiency; the point contact between particles has an effective thermal conductivity less than 1W m -1 K -1 , and local hot spots are easy to induce metal sintering and carbon deposition inactivation; the particles are easy to pulverize after long-term thermal cycling, producing fine powder to block the flow channel; limited by Knudsen / molecular diffusion resistance, the utilization rate of active sites on the outer surface and inner hole is less than 30%, and the amount of noble metal is high but difficult to further improve the apparent activity.
[0005] In recent years, some researchers have also tried to prepare monolithic catalysts by sol-gel, 3D printing or electrospinning technology, but there are common problems such as low slurry solid content (less than 15wt%), drying shrinkage cracking, insufficient strength of the carrier, etc., which cannot balance high loading, high specific surface area and low thermal stress. Therefore, it has become a technical bottleneck to be solved in the field to develop a propane POR catalytic structure with simple preparation process, small pressure drop, high heat / mass transfer efficiency, and deep coupling with SOFC thermal environment. SUMMARY
[0006] The technical problem to be solved by the present application is to provide a monolithic honeycomb ceramic catalyst for hydrogen production by propane partial oxidation reforming, a preparation method and application.
[0007] The technical solution of the present application to solve the above technical problem is as follows:
[0008] The present application provides a preparation method of a monolithic honeycomb ceramic catalyst for hydrogen production by propane partial oxidation reforming, wherein a catalyst slurry is coated on the pore wall of a silicon carbide honeycomb ceramic carrier by negative pressure driving, and the monolithic honeycomb ceramic catalyst is obtained after drying and calcination; the catalyst slurry comprises a noble metal precursor and a composite carrier, the noble metal precursor comprises platinum and palladium, and the composite carrier comprises nano cerium oxide and gamma-alumina.
[0009] Further, the mesh number of the silicon carbide honeycomb ceramic carrier is 300-600 mesh.
[0010] Further, the catalyst slurry further comprises a binder.
[0011] Further, the noble metal precursor is mixed with water in a mass ratio of 3:2 to obtain a mixed solution, 40%wt of the composite carrier and 1%wt of the binder are added to the mixed solution with a mass of 100%, and the mixture is ball milled to obtain the catalyst slurry.
[0012] Further, the method comprises the following steps:
[0013] S1, preparing a honeycomb ceramic carrier raw material into the silicon carbide honeycomb ceramic carrier, the composition of the honeycomb ceramic carrier raw material comprising SiC coarse particles, SiC fine particles, aluminum silicate reinforcing agent, sintering aid, binder forming agent and water;
[0014] S2, preparing the catalyst slurry;
[0015] S3, spraying the catalyst slurry on one end face of the silicon carbide honeycomb ceramic carrier, and driving the catalyst slurry into the pore of the honeycomb ceramic carrier and adhering to the pore wall by negative pressure on the other end face of the silicon carbide honeycomb ceramic carrier;
[0016] S4, drying and calcining to obtain the monolithic honeycomb ceramic catalyst.
[0017] Further, the particle size range of the SiC coarse particles is 25-50 μm, and the particle size range of the SiC fine particles is 0.5-10 μm.
[0018] Further, in the honeycomb ceramic carrier raw material, the mass percentage of the SiC coarse particles is 72%, and the mass percentage of the SiC fine particles is 15%.
[0019] Further, the pressure value of the negative pressure driving is 10 MPa.
[0020] The application further provides a monolithic honeycomb ceramic catalyst for hydrogen production by propane partial oxidation reforming, which is prepared by the method.
[0021] The application further provides application of the monolithic honeycomb ceramic catalyst in hydrogen production by propane partial oxidation reforming in SOFC, and the reaction is carried out under the conditions of normal pressure, a reaction temperature of 650 DEG C, an air speed of 5000-20000 h-1. -1
[0022] The application has the following beneficial effects:
[0023] (1) The monolithic honeycomb ceramic catalyst for hydrogen production by propane partial oxidation reforming is prepared by using a micro-channel type monolithic honeycomb ceramic as a carrier, which can greatly improve the specific surface area, is beneficial to uniform distribution of active substance sites in a composite active catalytic layer, and improves the conversion rate and reaction rate of the propane partial oxidation reforming reaction.
[0024] (2) The monolithic honeycomb ceramic catalyst for hydrogen production by propane partial oxidation reforming is prepared by using platinum and palladium in combination in the composition of the catalyst slurry, which has the advantages of low-temperature high activity, carbon deposition resistance, high selectivity, easy dispersion, sintering resistance, etc., and is particularly suitable for use in combination with a honeycomb ceramic carrier.
[0025] (3) The monolithic honeycomb ceramic catalyst for hydrogen production by propane partial oxidation reforming is prepared by single coating instead of traditional multi-step loading, and the preparation efficiency is significantly improved.
[0026] (4) The monolithic honeycomb ceramic catalyst for hydrogen production by propane partial oxidation reforming has high activity and selectivity: the propane conversion rate is greater than or equal to 90% at 650 DEG C, and the output power density is greater than 0.4 W / cm2. 2 BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 Fig. 1 is a structural schematic diagram of the monolithic honeycomb ceramic catalyst for hydrogen production by propane partial oxidation reforming of the application.
[0028] Figure 2 Fig. 2 is a schematic diagram of the negative pressure driving coating of the catalyst slurry in the preparation method of the application. DETAILED DESCRIPTION
[0029] The principles and characteristics of the application are described below, and the examples are only used to explain the application, and are not used to limit the scope of the application.
[0030] The method for preparing the monolithic honeycomb ceramic catalyst for propane partial oxidation reforming to produce hydrogen according to the present invention is characterized in that a catalyst slurry is coated on the pore wall of a silicon carbide honeycomb ceramic support by negative pressure driving, and the monolithic honeycomb ceramic catalyst is obtained after drying and calcination; the catalyst slurry includes a noble metal precursor and a composite support, the noble metal precursor includes platinum and palladium, and the composite support includes nano-cerium oxide and γ-alumina.
[0031] The preparation method of the monolithic honeycomb ceramic catalyst for propane partial oxidation reforming to hydrogen production of the present invention uses a microchannel monolithic honeycomb ceramic as a support, which can significantly increase the specific surface area, which is beneficial to the uniform distribution of active material sites in the composite active catalyst layer, and improves the conversion rate and reaction rate of propane partial oxidation reforming reaction. In the composition of the catalyst slurry, platinum and palladium are used in combination, which has the advantages of low temperature and high activity, anti-carbon deposition, high selectivity, easy dispersion, and resistance to poisoning and sintering. It is particularly suitable for use in combination with honeycomb ceramic support. At the same time, nano-cerium oxide and γ-alumina are added, and CeO2 passes through Ce 3+ / Ce 4+ Reversible regulation maintains reaction equilibrium while inhibiting carbon deposition and extending catalyst lifespan; alumina has a high specific surface area, which helps disperse active components and prevents agglomeration.
[0032] The monolithic honeycomb ceramic catalyst preparation method of the present invention can solve the problems of low reforming efficiency, large bed pressure drop and complicated preparation process of existing propane partial oxidation reforming hydrogen production catalysts. The preparation steps are simple, effectively improving the dispersion and utilization rate of noble metal active components, improving the catalytic activity and hydrogen yield of propane partial oxidation reforming, inhibiting the generation of by-product CO, and reducing the risk of SOFC anode poisoning.
[0033] Preferably, the silicon carbide honeycomb ceramic carrier has a mesh size of 300-600 mesh.
[0034] Preferably, the preparation method of the present invention includes the following steps:
[0035] S1. Prepare the silicon carbide honeycomb ceramic carrier raw material into the honeycomb ceramic carrier. The components of the honeycomb ceramic carrier raw material include coarse SiC particles, fine SiC particles, aluminum silicate reinforcing agent, sintering aid, binder forming agent and water.
[0036] Preferably, the particle size range of coarse SiC particles is 25-50 μm, and the particle size range of fine SiC particles is 0.5-10 μm.
[0037] Preferably, in the cellular ceramic carrier raw material, the mass percentage of coarse SiC particles is 72%, and the mass percentage of fine SiC particles is 15%.
[0038] S2. Prepare catalyst slurry;
[0039] Preferably, the catalyst slurry is prepared by mixing a precious metal precursor with water at a mass ratio of 3:2 to obtain a mixed solution, adding 40% wt of composite carrier and 1% wt of binder to 100% of the mass of the mixed solution, mixing and ball milling to obtain the catalyst slurry; the solid content of the catalyst slurry is 40%.
[0040] Preferably, the catalyst slurry also includes a binder, specifically silica sol and aluminum sol.
[0041] S3, such as Figure 2 As shown, a catalyst slurry is sprayed onto one end face of a silicon carbide honeycomb ceramic carrier, and the catalyst slurry is driven into the pores of the honeycomb ceramic carrier by negative pressure and adheres to the pore wall.
[0042] The pressure value for negative pressure drive is 10 MPa.
[0043] S4. Dry and calcine to obtain the monolithic honeycomb ceramic catalyst.
[0044] The monolithic honeycomb ceramic catalyst for propane partial oxidation reforming to produce hydrogen of the present invention was prepared by the method described above, and its structure is as follows: Figure 1 As shown.
[0045] The application of the monolithic honeycomb ceramic catalyst of the present invention in the propane partial oxidation reforming hydrogen production reaction of SOFC, under atmospheric pressure, reaction temperature of 650°C, and space velocity (GHSV) of 5000–20000 h⁻¹. -1 The reaction takes place under specific conditions.
[0046] After being preheated in the preheater, the propane mixture enters the monolithic honeycomb ceramic catalyst and undergoes the following reaction:
[0047]
[0048] The products after the reaction are passed through a condenser and a dryer in sequence to obtain hydrogen, carbon dioxide and carbon monoxide.
[0049] The present invention will be illustrated by specific embodiments below.
[0050] Example 1
[0051] Using a 300-mesh monolithic honeycomb ceramic catalyst, at a temperature of 650℃ and a space velocity of 5000 h⁻¹, -1 An integrated SOFC experiment was conducted under operating conditions with a water-to-carbon ratio of 0.8. After stable operation, the propane conversion rate was measured.
[0052] Examples 2-4 are all based on Example 1, the difference being the feed gas space velocity used in the SOFC integration performance test. The test parameters and performance evaluation indicators for Examples 1-4 are shown in Table 1.
[0053] Table 1. Test parameters and performance evaluation indicators for Examples 1-4
[0054]
[0055] Examples 5-9 are all based on Examples 1-4, the difference being that the monolithic honeycomb ceramic catalyst used in the SOFC experiments was 400 mesh. The test parameters and performance evaluation indicators for Examples 5-9 are shown in Table 2.
[0056] Table 2 Test parameters and performance evaluation indicators for Examples 5-8
[0057]
[0058] Examples 9-12 are all based on Examples 1-4, the difference being that the monolithic honeycomb ceramic catalyst used in the SOFC experiments was 600 mesh. The test parameters and performance indicators of Examples 9-12 are shown in Table 3.
[0059] Table 3 Test parameters and performance indicators for Examples 9-12
[0060]
[0061] Performance testing: After running for a certain period of time, test results showed that the propane conversion rate reached 90-97%, and the stack output power density was greater than 0.4 W / cm³. 2 .
[0062] Comparative Example 1
[0063] Referring to Example 1, the difference is that the catalyst used in the SOFC experiment was a single-component Pt catalyst.
[0064] Comparative Example 2
[0065] Referring to Example 1, the difference is that the catalyst used in the SOFC experiment was a single-component Pd catalyst.
[0066] Comparative Example 3
[0067] Referring to Example 1, the difference is that the catalyst support used in the SOFC experiment was γ-alumina.
[0068] Comparative Example 4
[0069] Referring to Example 1, the difference lies in the use of a 200-mesh monolithic honeycomb ceramic catalyst in the SOFC experiment. Currently, it is not possible to prepare honeycomb ceramic supports with higher pore density, making comparison impossible.
[0070] Comparative Example 5 is the same as Example 1, except that the monolithic honeycomb ceramic catalyst used in the SOFC experiment was prepared by impregnation, with a lower loading and uneven coating.
[0071] The test parameters and performance indicators of Comparative Examples 1-5 are shown in Table 4.
[0072] Table 4 shows the test parameters and performance indicators for Comparative Examples 1-5.
[0073]
[0074] The results of Examples 1-12 show that increasing pore density can simultaneously improve conversion efficiency and power density at high space velocities.
[0075] Comparative Examples 1-2 used Pt and Pd single-component catalysts at 5000h -1 At space speed, a conversion efficiency of 91.8% and an output power density of 0.45 W / cm³ were achieved. 2 With a conversion rate of 92.1% and an output power density of 0.47 W / cm³, 2 The conversion rate was 92.3% and the output power density was 0.45 W / cm³ compared to Example 1 (300 mesh). 2 The near-equal figures demonstrate that single precious metals offer no significant advantages, but rather have significant disadvantages due to their high cost.
[0076] Comparative Example 3, using γ-alumina as a support, yielded a conversion rate of only 88.6% and an output power density of 0.43 W / cm³. 2 The efficiency was lower than all honeycomb ceramic systems, highlighting the key role of three-dimensional regular channels in enhancing mass transfer and suppressing hot spots; the 200-mesh low-density carrier in Comparative Example 4 further reduced the conversion rate to 85.7% and the output power density to 0.42 W / cm³. 2 This indicates that insufficient pore density directly limits the active surface area and diffusion efficiency; the impregnation method in Comparative Example 5, due to low loading and uneven distribution, only achieved a conversion rate of 84.1% and an output power density of 0.41 W / cm³. 2 This demonstrates the importance of uniform coating in maintaining the integrity of the catalytic-electrochemical reaction interface.
[0077] In summary, 600-mesh honeycomb ceramics at 15000h -1 At a space velocity of 96.3% propane conversion and 0.59 W / cm², the propane conversion was achieved. 2 The output power density achieves peak performance, breaking through the traditional limits of 200-mesh carrier preparation while avoiding the high cost of precious metals.
[0078] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for producing a hydrogen production monolithic honeycomb ceramic catalyst for partial oxidation reforming of propane, characterized by, The catalyst slurry is coated on the pore wall of the silicon carbide honeycomb ceramic carrier, and the catalyst slurry is driven into the pore of the silicon carbide honeycomb ceramic carrier by negative pressure, and the monolithic honeycomb ceramic catalyst is obtained after drying and calcination; the catalyst slurry comprises a noble metal precursor and a composite carrier, the noble metal precursor comprises platinum and palladium, and the composite carrier comprises nano cerium oxide and γ-alumina.
2. The method of claim 1, wherein the method comprises the steps of: (a) mixing the catalyst precursor, the binder, and the pore forming agent to form a mixture; (b) extruding the mixture to form a green body; (c) drying the green body; (d) sintering the dried green body; and (e) calcining the sintered green body. The silicon carbide honeycomb ceramic carrier has a mesh number of 300-600.
3. The method for preparing a monolithic honeycomb ceramic catalyst for propane partial oxidation reforming to produce hydrogen according to claim 1, characterized in that, The catalyst slurry further comprises a binder.
4. The method for preparing a monolithic honeycomb ceramic catalyst for propane partial oxidation reforming to produce hydrogen according to claim 3, characterized in that, The catalyst slurry is prepared by mixing the noble metal precursor and water in a mass ratio of 3:2 to obtain a mixed solution, adding 40%wt of the composite carrier and 1%wt of the binder based on 100% of the mass of the mixed solution, mixing and ball milling to obtain the catalyst slurry.
5. The method for preparing a hydrogen production monolith honeycomb ceramic catalyst for partial oxidation of propane according to any one of claims 1 to 4, characterized in that, The method comprises the following steps: S1, preparing a honeycomb ceramic carrier raw material into the silicon carbide honeycomb ceramic carrier, the composition of the honeycomb ceramic carrier raw material comprising SiC coarse particles, SiC fine particles, aluminum silicate reinforcing agent, sintering aid, binder forming agent and water; S2, preparing the catalyst slurry; S3, spraying the catalyst slurry on one end face of the silicon carbide honeycomb ceramic carrier, and driving the catalyst slurry into the pore of the silicon carbide honeycomb ceramic carrier and adhering to the pore wall by negative pressure on the other end face of the silicon carbide honeycomb ceramic carrier; S4, drying and calcining to obtain the monolithic honeycomb ceramic catalyst.
6. The method of claim 5, wherein the catalyst is prepared by the steps of: (a) mixing the catalyst precursor with a binder to form a mixture; (b) extruding the mixture to form a green body; (c) drying the green body; (d) sintering the dried green body; and (e) calcining the sintered green body. The particle size of the SiC coarse particles ranges from 25 to 50 μm, and the particle size of the SiC fine particles ranges from 0.5 to 10 μm.
7. The method of claim 6, wherein the method comprises the steps of: (a) mixing the catalyst precursor with the binder to form a mixture; (b) extruding the mixture to form a green body; (c) drying the green body; (d) sintering the dried green body; and (e) calcining the sintered green body. In the honeycomb ceramic carrier raw material, the mass percentage of the SiC coarse particles is 72%, and the mass percentage of the SiC fine particles is 15%.
8. The method of claim 5, wherein the catalyst is prepared by the steps of: (a) mixing the catalyst precursor with a binder to form a mixture; (b) extruding the mixture to form a green body; (c) drying the green body; (d) calcining the dried green body; and (e) reducing the calcined green body. The pressure value of the negative pressure driving is 10 MPa.
9. A hydrogen-producing monolithic honeycomb ceramic catalyst for the partial oxidation reforming of propane, characterized in that, The monolithic honeycomb ceramic catalyst is prepared by the method of any one of claims 1-8.
10. Use of the monolithic honeycomb ceramic catalyst according to claim 9 in the partial oxidation reforming of propane to hydrogen in a SOFC, characterized in that, The reaction was carried out under normal pressure, at a reaction temperature of 650°C, and at a space velocity of 5000-20000h -1 -1.
Citation Information
Patent Citations
Method for preparing cordierite monolithic catalyst in variable-temperature vacuum coating mode
CN113941371A
Preparation method of honeycomb-type sulfur-resistant hydrophobic vanadium-titanium-based SCR (Selective Catalytic Reduction) catalyst
CN114588950A
Preparation method of catalyst for hydrogen production by reforming propane and carbon dioxide
CN117181279A
Coating type integral structure ammonia decomposition catalyst and preparation method thereof
CN118594534A
Self-heating catalysis propane partial oxidation reforming coupling tube type solid oxide fuel cell system and preparation method of catalyst and carrier of self-heating catalysis propane partial oxidation reforming coupling tube type solid oxide fuel cell system
CN120319848A